PENGARUH PEMBERIAN PUDING SARI PEPAYA TERHADAP PRODUKSI ASI PADA IBU POSTPARTUM DI BPM SUGIHARTI LUBUK PAKAM TAHUN 2020 - Nurul Azizah Hasibuan; Evi Desfauza (Poltekkes Kemenkes Medan, 2020)
Introduction: One of the obstacles that occur in postpartum mothers is not giving exclusive breastfeeding. According to UNICEF data (2018) the coverage of exclusive breastfeeding in the world is only around 36%. Papaya fruit provision to postpartum mothers is one of the efforts to increase breast milk production, the aim of this study was to find out the effect of papaya juice pudding provision to breast milk production in postpartum mothers at Sugiharti midwifery clinic of Lubuk Pakam in 2020. Methods: This type of research was Quasi Experiment with a Posttest Only Control Group design and the sampling used was purposive sampling. Samples were 30 postpartum mothers, namely 15 experimental groups who gave papaya juice pudding and 15 control groups who were not given papaya juice pudding with the inclusion criteria of normal postpartum mothers, infants who were given early breastfeeding initiation, mothers who did not consume drugs, herbal / Other breastfeeding smoothing supplements, willing to take part in the research through Informed Consent, were given in the experimental group papaya juice pudding while in the control group papaya juice pudding was not given. Results and Discussion: This research on giving papaya juice pudding was conducted for 7 consecutive days and then measured the volume of breast milk using Breastpump. Based on the results of the study showed that the average milk production of the experimental group was 128.00 and the average milk production of the control group was 91.20, so the difference in breast milk production was 36.8. Then it can be seen that the results of the Independent T-Test test obtained a P-Value of 0.000 (? <0.005). Conclusion: The provision of papaya juice pudding has an effect on increasing breast milk production in postpartum mothers. It is suggested to midwifery clinic to utilize papaya fruit which can be processed into papaya juice pudding to increase breast milk production in postpartum mothers so that mothers give exclusive breastfeeding to their babies.